Penerapan Permainan Wordwall untuk Meningkatkan Kosa Kata Bahasa Jawa pada Siswa Kelas 4 SD Negeri 3 Bucu Jepara - Nur Ayu Saputri; Khoirunnisa Salsabila Nafi'ah; Syailin Nichla Choirin Attalina (Lembag, 2024)
This research aims to increase the Javanese vocabulary of fourth grade students at SD Negeri 3 Bucu Jepara through the use of Wordwall games. The method used in this research is Classroom Action Research (CAR)using the Kemmis and Mc Taggart model, wich consists of two cycles. Each cycle includes the stages of planning, implementation, observation and reflection. The research subjects consisted of 10 class IV students. Data was obtained through observation and tests. The research results show that using the wordwall game can increase students' interest and ability in learning Javanese vocabulary. In the first cycle, teacher activities got a percentage of 85% and students got a percentage of 91%, which was good but still needed improvement, while in the second cycle, teacher activities got a percentage of 97.5% and students reached 95%, getting a very good category with a significant increase in student test results. The implications of this research show that interactive learning media such as wordwalls are effective in improving student learning outcomes in learning Javanese.